The ferryman : a novel [large type] - Cronin, Justin (Random House Large Print, 2023)
On the island utopia of Prospera, a ferryman who gently shepherds people through the retirement process--and, when necessary, enforces it--Proctor Bennet, of the Department of Social Contracts, receives a disturbing and cryptic message from his father, while The Support Staff, who keep Prospera running, organize a revolution that causes Proctor to question everything he once believed.